Stem Mortality and Forest Dieback in a 20-Years Experimental Drought in a Mediterranean Holm Oak Forest - Ogaya, Romà; Liu, Daijun; Barbeta, Adrià; Peñuelas, Josep (Frontiers in Forests and Global Change, 2020)
Climatic warming is predicted to increase the intensity and duration of extreme weather such as droughts and heat waves. Climate change could therefore increase stem mortality and forest dieback in many ecosystems around the world, especially in semi-arid forests. We investigated the influence of climatic conditions and a throughfall displacement experimental treatment (15% decrease in the amount of soil moisture) on the intensity of stem mortality in a Mediterranean forest. We also investigated the use of remotely sensed data from MODIS as a tool to estimate the intensity of stem mortality and a possible strategy of forest management to mitigate this forest dieback induced by climate change. Stem mortality was higher when mean annual temperature was higher and rainfall was lower, especially during spring and summer. Mortality was higher and more affected by the drought treatment in the holm oak, Quercus ilex, than in co-occurring species of tall shrubs better adapted to drier conditions. Two spectral MODIS indices (NDVI and EVI) were good predictors of stem mortality, but others (GPP, PsnNet, and NPP specifically calculated to predict forest health and development) were not clearly correlated with stem mortality. Selective stem thinning strongly reduced stem mortality (especially in Q. ilex) by buffering the effects of climate change on forest structure. Finally, the possible future substitution of the current dominant species of this forest, Q. ilex, by species of tall shrubs better adapted to drought is also discussed.